The Effect Of Car, Nom, Profit- Loss Sharing Financing And Liquidity On Profitability In Islamic Commercial Banks And Islamic Business Units In Indonesia - Didik Gunawan; Saparuddin Siregar; Isnaini Harahap (Proceeding International Seminar of Islamic Studies, 2019)
This aims of this study is to determine the effect of CAR, NOM, profit- loss sharing financing and liquidity on ROA in Islamic commercial banks and Islamic business units in Indonesia. The results of evaluations using SPSS 25 show CAR, profit sharing financing and liquidity show no significant effect on ROA in Islamic commercial banks and Islamic business units in Indonesia, while NOM has a significant effect on ROA in Islamic commercial banks and Islamic business units in Indonesia.